1985
DOI: 10.1002/aja.1001730105
|View full text |Cite
|
Sign up to set email alerts
|

Motor innervation of intrafusal fibers in rat muscle spindles: Incomplete separation of dynamic and static systems

Abstract: Distributions of 53 motor axons to different types of intrafusal fibers were reconstructed from serial 1-micron-thick transverse sections of 13 poles of spindles in the rat soleus muscle. The mean number of motor axons that innervated a spindle pole was 4.1. Approximately 60% of motor axons lost their myelination prior to or shortly after entry into the periaxial fluid space of spindles. Motor innervation to the juxtaequatorial portion of nuclear bag fibers (particularly the bag1) consisted of groups of short,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The distribution of sensory and motor endings was similar to that described previously for rat spindles. 59,60 Altogether the patterns of MHC expression of 62 intrafusal fibers in 15 spindles were examined.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of sensory and motor endings was similar to that described previously for rat spindles. 59,60 Altogether the patterns of MHC expression of 62 intrafusal fibers in 15 spindles were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Chain fibers in rat muscle spindles exhibit a simple pattern of motor innervation; typically, one relatively large endplate per pole located in the B or C region of the fiber (Walro and Kucera, 1985;Walro, unpublished data). No small ectopic endplates or multiple endplates were observed on chain fibers.…”
Section: Deafferented Musclesmentioning
confidence: 95%
“…Indeed, these are the isoforms expressed by chain fibers in the absence of sensory innervation. Likewise, bag 1 fibers express type 1 MHC and occasionally possess motor endplates in their extracapsular region, which is suggestive of ␤-innervation (Kucera et al, 1978;Walro and Kucera, 1985). They can be coinnervated with type 1 extrafusal fibers by dynamic ␤-motorneurons in the cat (Jami et al, 1982;Kucera and Walro, 1986).…”
Section: Deafferented Musclesmentioning
confidence: 96%
“…The type of myotube contacted by sensory or motor neurons may also be a factor in expression of slowtonic MHC. Only nuclear bag fibers but not nuclear chain express slow-tonic MHC (Pierobon-Bormioli et al 1980), even though a single primary afferent innervates both bag and chain intrafusal fibers (Walro and Kucera 1985).…”
Section: Regulation Of the Slow-tonic Mhcmentioning
confidence: 99%
“…It has therefore been suggested that the afferent innervation may upregulate expression of slowtonic MHC in the myotubes that give rise to nuclear bag 2 and nuclear bag I fibers (Kucera and Walro 1991). However, the relationship between afferent innervation and expression of tonic MHC is not simply cause-and-effect because nuclear chain intrafusal fibers do not express slow-tonic MHC even though a single primary afferent innervates both nuclear bag and nuclear chain fibers (Pierobon-Bormioli et al 1980;Walro and Kucera 1985).…”
Section: Introductionmentioning
confidence: 99%